Financial Statement Analysis to assess financial performance at PT. Gudang Garam Tbk - M Farid Amriyadi; Rahimah br. Purba; Oktarini Khamilah Siregar (Yayasan Multidimensi Kreatif, 2024)
This study aims to provide an assessment of the financial condition and performance of PT. Gudang Garam Tbk during the period 2012-2016.this research method is Descriptive quantitative, namely collecting, processing and interpartying the data obtained so as to obtain an overview of the financial condition and performance of PT. Gudang Garam Tbk during the period 2012-2016.The results of this study show that the company's work of PT. Gudang Garam Tbk Indonesia based on the calculation results of liquidity ratio analysis can be said to be not good enough because the company will have difficulties in paying off current obligations. Company performance PT. Gudang Garam Tbk based on solvency ratio analysis is also quite good where every year it always increases. This is due to the low expenditure of companies sourced from loans. Company performance PT. Gudang Garam Tbk uses activity analysis which is also quite healthy where every year it increases every year. This is maintained so that users of company assets every year are more efficient and effective. 4. Company performance of PT. Gudang Garam Tbk based on calculations using profitability ratio analysis is quite good where every year it increases and only one year decreases because every year the profit owned by the company from each asset increases.